2023
DOI: 10.3389/fcell.2023.1083401
|View full text |Cite
|
Sign up to set email alerts
|

MAPKs in the early steps of senescence implemEMTation

Abstract: Evidence is accumulating that the earliest stages of the DNA damage response can direct cells toward senescence instead of other cell fates. In particular, tightly regulated signaling through Mitogen-Activated Protein Kinases (MAPKs) in early senescence can lead to a sustained pro-survival program and suppress a pro-apoptotic program. Importantly, an epithelial-to-mesenchymal Transition (EMT)-like program appears essential for preventing apoptosis and favoring senescence following DNA damage. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 142 publications
0
1
0
Order By: Relevance
“…Several other studies [ 40 42 ] have shown that this pathway is involved in cell proliferation, differentiation, and apoptosis, making it an important signaling pathway. In mammals, MAPK can be translated as “mitogen-activated protein kinase” Regulating cell proliferation, differentiation, movement, and survival is one of the important pathways affecting testis development and spermatogenesis [ 43 ]. This suggests that the MAPK signaling pathway plays a critical role in regulating rooster testis development, spermatogenesis, and sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies [ 40 42 ] have shown that this pathway is involved in cell proliferation, differentiation, and apoptosis, making it an important signaling pathway. In mammals, MAPK can be translated as “mitogen-activated protein kinase” Regulating cell proliferation, differentiation, movement, and survival is one of the important pathways affecting testis development and spermatogenesis [ 43 ]. This suggests that the MAPK signaling pathway plays a critical role in regulating rooster testis development, spermatogenesis, and sperm quality.…”
Section: Discussionmentioning
confidence: 99%